Low energy availability surrogates associated with lower bone mineral density and bone stress injury site. Issue 5 (16th May 2022) - Holtzman, Bryan; Popp, Kristin L.; Tenforde, Adam S.; Parziale, Allyson L.; Taylor, Kathryn; Ackerman, Kathryn E.
Abstract: Background: Exercise is an osteogenic stimulus that should increase bone mineral density (BMD) and protect against injury. However, some female athletes have lower BMD and increased bone stress injury (BSI) risk. Impaired bone health seen in athletes may be explained by low energy availability as described by concepts of Relative Energy Deficiency in Sport (RED‐S) and Female Athlete Triad (Triad). Objective: To elucidate the relationship between RED‐S/Triad risk factors and BSI to high‐risk (femoral neck, sacrum) and low‐risk (other) bones. Design: Cross‐sectional survey and retrospective chart review. Setting: Tertiary care academic center. Patients: Female athletes aged 15–30 years participating in ≥4 h/week of exercise presenting to sports medicine/orthopedics clinic who had a self‐reported BSI and available dual‐energy x‐ray absorptiometry (DXA) measurement of BMD. Interventions: Not applicable. Main Outcome Measurements: Location of BSI. Results: In 127 athletes, high‐risk BSI was associated with surrogates of low energy availability ( p = .032) and having a DXA Z‐score < −1 ( p = .035) but not a current/past history of menstrual dysfunction ( p = .348). Accumulating RED‐S/Triad risk factors increase the odds of incurring a high‐risk BSI ( p = .048). Conclusions: Adolescent/young female athletes who sustain BSI at high‐risk sites (femoral neck, sacrum) may have underlying risk factors (eg, low energy availability, poor overall bone health) that should prompt further workup and referral to optimize health in these athletes.